Prevalence and causes of self-medication for oral health problems: a systematic review and meta-analysis - Katayoun Katebi; Hosein Eslami; Saba Jabbari (BMC, 2024)
Abstract Introduction Self-medication, particularly for oral and dental health problems, stands as a significant health and social concern. Therefore, the current systematic review and meta-analysis study was conducted to evaluate the prevalence and underlying causes of self-medication for oral and dental health problems. Method Articles published until August 30, 2023, were searched in Scopus, PubMed, and Web of Science databases. A manual search was also done in Google Scholar, references, citations, and Gray literature. The screening of articles was done independently by two members of the research team. The quality of reporting in the articles was evaluated using the JBI Critical Appraisal Checklist For Analytical Cross-Sectional Studies. Meta-analysis was performed using the fixed effects model in Stata software (StataCorp, version 16). Results The results of 37 studies involving 12,110 participants with a mean age of 32 years and 48% male were analyzed. Most of the studies were conducted in low- and middle-income countries. The overall prevalence of self-medication was estimated at 59% [95%CI: 55-63%], with 58% [95% CI: 53-63%] among dental patients, and 60% [95% CI: 52-67%] in the general public. Analgesics (60%) and antibiotics (19%) were the most commonly used drug categories. In terms of the mean proportion, having previous experience, unbearable pain, and lack of time had the highest percentages, and in terms of the number of repetitions among the reviewed articles, economic problems, lack of time, and limited access were the most repeated reasons. The most significant related factors in self-treatment were female gender, higher education, and occupation. Pharmacies were the primary source of self-treatment medications. Conclusion The results showed a very high prevalence of self-medication for oral health problems, necessitating prompt and effective interventions. It is recommended to focus on regulating the consumption of analgesics and antibiotics, addressing financial issues, and overseeing the pharmacy operations.